The effectiveness of regional active labour market policies to fight against unemployment: an analysis for Catalonia - Raúl Ramos; Jordi Suri\~nach; Manuel Artís (Institute for the Study of Labor (IZA), 2009)
The aim of this work is to assess the effectiveness of active labour market policies carried out by the Catalan Public Employment Services (SOC) during the year 2005. The results obtained from the application of matching techniques show that the probability of finding a job for an individual who participated in any of the analyzed SOC's actions is 5 percentage points higher in relation to those who did not participate. The individual analysis of the different programs has shown the effectiveness of the greater part of the actions carried out. Last, the results have also highlighted the further improvement of the combination of some of the actions.
Keywords: C31; J64; J68; 330; Active labour market policies; unemployment; propensity score matching; Arbeitsmarktpolitik; Berufliche Integration; Wirkungsanalyse; Arbeitslosigkeit; Beschäftigungseffekt; Katalonien; Regionaler Arbeitsmarkt; Spanien